PERAN KADER KESEHATAN DALAM PROMOSI PENCEGAHAN KOMPLIKASI HIPERTENSI DI WILAYAH PERKOTAAN: LITERATUR REVIEW - Istifada, Rizkiyani; Rekawati, Etty (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2019)
Hypertension have been a trend of urban health problems. One of prevention hypertension’scomplications is to assist in families by community health workers. Community health nurseshave a role to provide community health workers assistance and supervision. The partnership doimplementation between nurse and community health worker to manage the Health City’sprogram in Indonesia. However, the phenomenon occurring in Indonesia shows a lack of supportgiven for community health workers to be involved in implementing health promotion. Thisliterature review describes the involvement of community health workers to prevention ofcomplications of hypertension in the community. This study uses the literature review method byusing search on online database in Cambridge Core e-resources, Wiley Online, andScienceDirect with the publication period of articles from 2008-2018. The result of literature search show 15 articles that focused on the role of community health workers to prevention ofhypertensive complications. The studies show that the community health worker have beeneffective to prevent hypertension’s complications. The involvement of community health workerscan be done by providing self-management assistance to improve healthy lifestyle, such asmotivating physical activities and limiting salt consumption. In general, the chosen communityhealth workers are women, willing to be involved in health promotion efforts, and be able tocommunicate and make a report. The ability of community health nurses is needed to provide andmaximize community empowerment.